The perception of younger generation about the portrayal of Malay identity in today's Malay movies / Siti Nur Farrah Faadiah Ab Ghani ... [et al.] - Ab Ghani, Siti Nur Farrah Faadiah; Ibrahim, Mohamad Razif; Abd Latiff, Dzaa Imma; Ismail, Siti Nasarah (2015)
This paper is aimed to study about the perception of younger generation about the portrayal of Malay identity in today's Malay movies. It is understood that younger generation nowadays prone to understand that Malay identity must revolve around kain batik, sarong, tanjak, keris and etc. The acceptance of the idea of Malay identity seems to stop at black-and-white movies, making it hard for today's film makers to find out the way to make a Malay movie enriched with Malay flavor. Furthermore, fierce competition from the West which equipped with technologies and exceptional new concepts give an extra pressure for our local movies to be with the mainstream. Upon completing this research, researchers found out that younger generation does have their very own preferences with movies shown on the television and cinema. However, they also agreed to the fact that they are impressed at how 1950s and 1960s Malay classical movies especially the P.Ramlee's are still stay dearly to the hearts of audiences up until today. Though the findings reported young generation finds it is gratifying for them to watch Hollywood movies, the result indicates that they do somehow look forward to discover what the grandmothers and grandfathers have done back then in maintaining a sense of our real Malay identity to be portrayed in the movies for a remarkable quality Malay movie has proven to serve its society for a really long time.